2020
DOI: 10.32598/sija.13.10.180
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Activities of Daily Living and Depression in Older Adults

Abstract: Objectives: Physical inability to perform daily activities is one of the major causes of depression in the elderly and, on the other hand, depression can cause loss of interest in daily activities and lack of independence. The present study was aimed to assess the ability to perform activities of daily living (ADL) and instrumental activities of daily living (IADL) in the elderly and its relationship with depression in Maneh Samalghan city in 2017. Methods and materials: The present cross-sectional study was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…However, it should be noted that being single, especially during the elderly, does not necessarily increase depression. In the present study, no significant relationship was found between depression and age and the level of education, which is consistent with the results of the study conducted by Mohammadzadeh et al (7). In this study, no significant relationship was found between depression and gender, which is consistent with the results of the study conducted by Bakhtiyari et al (8).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, it should be noted that being single, especially during the elderly, does not necessarily increase depression. In the present study, no significant relationship was found between depression and age and the level of education, which is consistent with the results of the study conducted by Mohammadzadeh et al (7). In this study, no significant relationship was found between depression and gender, which is consistent with the results of the study conducted by Bakhtiyari et al (8).…”
Section: Discussionsupporting
confidence: 92%
“…However, in a study conducted by Iaboni et al (26) reported no association between depression and fear of falling among older adults, which is not consistent with the results of the present study. A significant and direct relationship was found between marital status and depression, which is consistent with the results of studies conducted by Pandit (27) and Mohammadzadeh et al (7).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result shows that the family was the main source of support for the studied older adults. Also, our analysis shows that 1.3% of older adults reported a low perceived social support score,[ 12 13 14 15 16 17 18 19 ] 42.1% reported an average score,[ 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 ] and 56.6% reported a high perceived social support score (above 40).…”
Section: Resultsmentioning
confidence: 70%
“…This finding is consistent with the results of the 2015 Iranian census, which revealed that more than half of Iranian seniors (about 54%) are illiterate. [ 33 34 ] Increasing literacy is related to health promotion literacy, which can lead to self-care, healthy aging, and reduced dependency. [ 35 ]…”
Section: Discussionmentioning
confidence: 99%